Morphological inequities? Numerical simulation of cervical spine injuries in rugby - Laniece, A.; Brauge, D.; Laville, A.; Skalli, W.; Laporte, S. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
The purpose of this study was to identify cervical spine morphologies at risk in rugby games. A parameterized osteoarticular finite element model of the cervical spine modeled 17 subjects under three different loadings, each being representative of rugby game phases: scrum (unconstrained axial compression), tackle (full-constraint axial compression) and collapsing scrum (hyperflexion). Stress and strain in the spine were recorded to determine appearances of injuries. The comparison of these injuries with the literature validated the model for injury prediction. A correlation analysis linked parameters of the morphology with the injury prediction and key parameters such as articular facet orientation arose. Precisely identifying all these parameters could help designing preventive clinical guidelines for rugby players.